Synthesis of Quinine-Triazole Derivatives (QNTDs) with Antifungal Potency - Sahu, Adarsh; Agrawal, Ramkishore (Anti-Infective Agents, 2022)
Background: Reduced efficacy of the available antifungal drugs is the major public health concern of the population all over the world. Despite significant advances in the treatment of these life-threatening infections, severe toxicity and increasing median effective dose have limited the efficacy of frontline therapy applicable against them. Objective: The quintessential occurrence of systemic toxicity handicaps the clinical utility of currently available antifungal drugs. 1,2,3-Triazoles in the same context are relatively less toxic. Consequently, conjugation of quinine with the triazole moiety for enhanced efficacy and reduced toxicity have been excessively envisaged and reported in the context of a range of activities ranging from inflammation to cancer, however lack of toxicity profile sabotages the translation of the laboratory prototype into successful clinical practice. Methods: We herein report the synthesis and characterization of a series of quinine triazole hybrids via o-mesylation followed by azide displacement, then reacting it with aliphatic and aromatic alkynes in water: t-butanol mixture. The reaction was carried in the presence of copper sulphate and sodium ascorbate. Product 6a-s was screened for in-vitro antifungal activity. The in-vitro antifungal potential of synthesized compounds was estimated against prominent fungal strains (Candida albicans, Aspergillus niger and, Aspergillus clavatus). Results: The results showed that some of the synthesized compounds exhibited marked activity. Compounds 6a, 6b, 6c, 6d, 6g, and 6q showed significant antifungal activity at micromolar concentration. The studies revealed that some of the compounds exhibited activities more than that of reference drugs. The compound containing thiazole ring 6c is the most potent compound of the series. Conclusion: Compound 6c was found to be the most vigorous against C. albicans, A. niger, A. clavatus with MIC values of 119.4, 112.7, and 121.3 μM/mL, respectively. Our SAR study revealed that the introduction of the 1,2,3-triazole ring in the structure of quinine modulated its potency for treating fungal infection.
Keywords: aspergillus niger